Pro SQL Server 2012 Relational Database Design and Implementation - Davidson, Louis; Moss, Jessica M.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2012)
Learn effective and scalable database design techniques in a SQL Server environment. Pro SQL Server 2012 Relational Database Design and Implementation covers everything from design logic that business users will understand, all the way to the physical implementation of design in a SQL Server database. Grounded in best practices and a solid understanding of the underlying theory, Louis Davidson shows how to (3z(Bget it right(3y (Bin SQL Server database design and lay a solid groundwork for the future use of valuable business data. Gives a solid foundation in best practices and relational theory Covers the latest implementation features in SQL Server Takes you from conceptual design to an effective, physical implementations
Keywords: Computer science; Database management; Computer Science; Computer Science, general; Database Management